UJI AKTIVITAS IMUNOGLOBULIN M (IgM) KELINCI JANTAN (Oryctolagus cuniculus) AKIBAT PENGARUH PEMBERIAN PRODUK MADU - Asriani Suhaenah; Nurul Ilmi Ainun Nissa (As-Syifaa Jurnal Farmasi, 2013)
The objective was to study the effect of natural pure honey on the immunoglobulin M (IgM) antibody activity against sheep red blood cells (SRBCs) antigen ini male rabbit (Oryctolagus cuniculus) using the hemoagglutination method. Three different honey products with 2,1 ml/kg body weight given orally twice a day for 5 days. Then each animal was injected intraperitoneally with 2,8 ml of 2% SRBCs. At day 7 after the immunization, serum were collected from the blood samples to know which highest dilution value of rabbit serum still showing agglutination reaction. The result of the the statistical analysis using the Complete Random Device ( CRD) method and than continued with the Duncan’s Multiple Range Test (DMRT) method shows that the administration of three different honey products  significantly increase Immunoglobulin M (IgM) activity against SRBCs. Key words : Honey, Hemaglutination, Rabbit